COMPARATIVE EVALUATION OF THE EFFECT OF MODERNIZATION ON THE STRESS-STRAIN STATE OF THE BOGIE LOCOMOTIVE VL60 - Hrushchak, I. M. (Science and Transport Progress, 2008)
In the paper the results of stressed-and-strained state calculations of the fragment of bogie frame supporting structure in the manufacturer’s variant and modernized one are presented. It is demonstrated that the proposed variant of modernization leads to reduction of stresses of the most loaded unit.